Weekly Variations of Intracerebral Hemorrhage Occurrence Among Different Populations: A Cross-Sectional Study - Pu, Yun-Tao; Yan, Ning; Wang, En-Yuan; Wang, Yan-Yue (Frontiers in Neurology, 2021)
Background and Purpose: The causes of higher incidence on a given day in intracerebral hemorrhage (ICH) were unclear. Previous studies have shown that it may vary by region and population. The purpose of our study was to confirm whether there was a weekly variation in ICH occurrence in southwest China, and whether differences existed among different population. Methods: In our hospital-based study, patients with first-onset ICH were screened from January 1, 2012, to December 31, 2019. We analyzed the weekly variation in ICH occurrence and stratifying by sex, age, comorbidities, living habits, and residence. Results: A total of 5038 first-onset ICH patients were enrolled in our study. Overall, more ICH occurred on Monday (OR, 1.22; 95% CI, 1.09-1.36; P<0.001) and Friday (OR, 1.15; 95% CI, 1.03-1.28; P<0.001) among all patients, and this pattern was consistent with men, whereas women had a higher incidence on Monday, Saturday, and Sunday. The increase in the number of ICH events on Monday and Friday was pronounced in Age of 41 to 60, however, no significant weekly variation in ICH occurrence was observed among other age strata. After stratifying by comorbidities, we observed a significant weekly variation in ICH occurrence in the patients with comorbidities of hypertension or diabetes. Smoking and drinking of alcohol were associated with a higher incidence of ICH on Friday, otherwise Monday excess was observed. The urban population demonstrated a significant weekly variation in ICH occurrence, whereas the rural population did not. Conclusions: We observed a weekly variation in ICH occurrence in southwest China, which was significantly affected by sex, age, comorbidities, living habits, and residence. Our study provided evidence that weekly variation in ICH occurrence may be dependent on region and population.